Human microRNA-299-3p decreases invasive behavior of cancer cells by downregulation of Oct4 expression and causes apoptosis - Göhring, Axel Robert; Cheng, Xinlai; Theobald, Jannick; Wölfl, Stefan (PLOS ONE, 2017)
Purpose Oct4 was reported to be one of the most important pluripotency transcription factors in the biology of stem cells including cancer stem cells, and progressed malignant cells. Here we report the investigation of gene expression control of Oct4 by selected human microRNAs and the physiological effect of Oct4 silencing in invasive cancer cells. Methods and results High throughput luciferase activity assay revealed the microRNA-299-3p to be the most effective in reducing gene expression of Oct4, which was confirmed by Western blot analysis and Oct4 promoter activity in a target luciferase assay. Furthermore, it could be demonstrated that downregulation of Oct4 by microRNAs-299-3p in breast cancer and fibrosarcoma cells lead to a decreased invasiveness in a microfluidic chip assay. Additionally, microRNA-299-3p causes apoptosis in cancer cells. Comparison with Oct4 specific siRNA transfection confirmed that this effect is primary due to the blockade of Oct4 expression. Conclusion The results suggest that microRNA-299-3p is an interesting target for potential clinical use. It may be able to decrease invasive behaviour of carcinoma cells; or even kill these cells by causing apoptosis.